Deregulierung des Marktes für schienengebundenen Containertransport in Indien. Eine Chance für internationale Eisenbahnen? - Merkert, Rico; Singh, Manoj (Deutscher Verkehrs-Verl., 2008)
Die Einführung von Wettbewerb in Eisenbahnmärkten ist seit einiger Zeit eine Thematik von weltweit großem Interesse. Während dieser Prozess in Europa über die Implementierung von EU-Richtlinien und in den USA durch die dortige Deregulierung weit voran getrieben wurde, gibt es in Asien und anderen Teilen der Welt immer noch viele Länder, in denen Liberalisierungsansätze bisher nur wenig vorangeschritten sind. Während für internationale Eisenbahnen im Zukunftsmarkt Schienengüterverkehr vor allem Osteuropa und China von Interesse scheinen, finden andere asiatische Staaten bisher weniger Beachtung. difu

The paper analyses the policy followed by the Indian Railways in opening up its intermodal freight segment to competition. This approach attempts to promote competition within the existing structure of integrated monopoly operation. The paper reports on a survey carried out after the policy announcement amongst new entrants to explore the principal barriers to competitive entry and draws some tentative conclusions about the Indian Railway model of deregulation. Access to land for terminals and uncertainty of haulage charges have emerged as crucial barriers although they have not deterred entry. Given the expected continuation of strong growth of the container business, there should be interesting opportunities for international railways with strong financial resources (for land, wagons and registration fees) or related businesses in the Indian intermodal (container) transport market. difu
Deregulation of intermodal rail freight transport in India.
Keywords: Verkehr; Güterverkehr; Schienengüterverkehr; Containerverkehr; Eisenbahn; Wettbewerb; Seehafen; Seeschiffsverkehr; Verkehrsmarkt; Deregulierung; Liberalisierung; Modal Split